Smart helmet using internet of things - Mohamed A. Torad; Mustafa Abdul Salam (Institute of Advanced Engineering and Science, 2021)
The rate of death relative to the size of the world’s population has remained constant, according to the world health organization (WHO). WHO targets to minimize the ratio of road death to the half by 2022. This paper discusses a way for accident detection and notification which can decrease this ratio. Piezoelectric sensors used inside a helmet to detect degree of trauma which interpret into electrical signal that used to determine if trauma is serious or not based on predetermined threshold. This trauma can be occuard due to any kind of accidents. So, this paper established a detection system to request instant help from emergency department and relatives by delivering them an SMS contains the latitude and longitude. In usual mode helmet can operate as tracking tool monitored by the relatives.